Stabilization of partially folded states in protein folding/misfolding transitions by hydrostatic pressure - Ferreira,S.T. (2005)
In the last few years, hydrostatic pressure has been extensively used in the study of both protein folding and misfolding/aggregation. Compared to other chemical or physical denaturing agents, a unique feature of pressure is its ability to induce subtle changes in protein conformation, which allow the stabilization of partially folded intermediate states that are usually not significantly populated under more drastic conditions (e.g., in the presence of chemical denaturants or at high temperatures). Much of the recent research in the field of protein folding has focused on the characterization of folding intermediates since these species appear to be involved in a variety of disease-causing protein misfolding and aggregation events. The exact mechanisms of these biologicalphenomena, however, are still poorly understood. Here, we review recent examples of the use of hydrostatic pressure as a tool to obtain insight into the forces and energetics governing the productive folding or the misfolding and aggregation of proteins.